2020
DOI: 10.19102/icrm.2020.110701
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Imaging for Atrial Fibrillation Ablation: Is There a Potential to Improve Procedural Outcomes?

Abstract: Since the introduction of atrial fibrillation (AF) ablation in the 1990s, the procedure has continuously evolved, with gradual improvements in outcomes and safety. Recent technological advancements include the introduction of contact force catheters and high-resolution electroanatomical mapping systems, while imaging modalities including transesophageal echocardiography and fluoroscopy have become integral parts of AF ablation procedures. Further, intraprocedural intracardiac echocardiography and the integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
(77 reference statements)
0
8
0
6
Order By: Relevance
“…Catheter ablation has been established as a standard treatment for symptomatic AF and PVI has become the cornerstone of such treatment, as recommended in the current guidelines (8) . Several studies have shown that advanced cardiac imaging techniques can improve AF ablation result (9,10) . Both CT scan and CMR provide accurate anatomic details (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter ablation has been established as a standard treatment for symptomatic AF and PVI has become the cornerstone of such treatment, as recommended in the current guidelines (8) . Several studies have shown that advanced cardiac imaging techniques can improve AF ablation result (9,10) . Both CT scan and CMR provide accurate anatomic details (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Medical images can offer crucial information for the evaluation and treatment of AF patients, and have been widely used in the ablation process ( Tops et al, 2010 ; Obeng-Gyimah and Nazarian, 2020 ). Table 4 summarizes the common imaging modalities used in three ablation stages (before, during, and after catheter ablation), mainly referring to Tops et al (2010) and Obeng-Gyimah and Nazarian (2020) . One can see that diverse imaging modalities have been introduced in the ablation process, each of which assists in various aspects of the procedure.…”
Section: Imaging Of Atrial Fibrillationmentioning
confidence: 99%
“…PV anatomy can also be measured by TEE, achieving up to 95% concordance with MRI ( Toffanin et al, 2006 ). Moreover, cardiac MRI remains the gold standard for fibrosis assessment ( Obeng-Gyimah and Nazarian, 2020 ). Especially, LGE MRI appears to be a promising alternative for pre-ablation scar visualization and quantification ( Siebermair et al, 2017 ).…”
Section: Imaging Of Atrial Fibrillationmentioning
confidence: 99%
“…Medical images can offer crucial information for the evaluation and treatment of AF patients, and have been widely used in the ablation process (Tops et al, 2010;Obeng-Gyimah and Nazarian, 2020). Table 5 summarizes the common imaging modalities used in three ablation stages.…”
Section: Imaging Of Afmentioning
confidence: 99%